Wheel-rail wear simulation and rail cant optimisation based on railway vehicle dynamics. Issue 1 (24th February 2021) - Li, Wei; Wang, Pu; Wang, Shuguo; Si, Daolin; Yang, Dongsheng
A numerical prediction model for the wheel-rail wear development on heavy-haul railway is established herein, and a corresponding program is written using MATLAB. Using Archard's material wear theory, wear distributions in the wheel-rail contact patch and along the rail profile are evaluated via vehicle-track dynamics simulation and wheel-rail rolling contact analysis. The established model is employed to study the influences of rail cant on the wheel-rail wear distribution and development. The following main conclusions are drawn. On straight railway section, the wheel-rail contact region and wear distribution become unreasonable when the rail cant exceeds 1/20. On curved section, the influences of rail cant on the wear of the inner and outer rails are different. The changes of rail cant also obviously impact the changing rules of wear with the vehicle speed. A rail cant of 1/30 is recommended for the curved section of heavy-haul railway.